Stimulus Onset Hub: an Open-Source, Low Latency, and Opto-Isolated Trigger Box for Neuroscientific Research Replicability and Beyond - Davis, Charles E.; Martin, Jacob G.; Thorpe, Simon J. (Frontiers in Neuroinformatics, 2020)
Accurate stimulus onset timing is critical to almost all behavioral research. Auditory, visual, or manual response time stimulus onsets are typically sent through wires to various machines that record data such as: eye gaze positions, electroencephalography, stereo electroencephalography, and electrocorticography. These stimulus onsets are collated and analyzed according to experimental condition. If there is variability in the temporal accuracy of the delivery of these onsets to external systems, the quality of the resulting data and scientific analyses will degrade. Here, we describe an approximately 200 dollar Arduino based system and associated open-source codebase that achieved a maximum of 4 microseconds of delay from the inputs to the outputs while electrically opto-isolating the connected external systems. Using an oscilloscope, the device is configurable for the different environmental conditions particular to each laboratory (e.g. light sensor type, screen type, speaker type, stimulus type, temperature, etc). This low-cost open-source project delivered electrically isolated digital stimulus onset Transistor-Transistor Logic triggers with an input/output delay of 4 microseconds, and was successfully tested with 7 different external systems that record eye and neurological data.